Periapical injection of betamethasone to control postoperative pain in emergency endodontic care - a randomized double blind clinical trial - Marcos Luciano Pimenta Pinheiro; Ricardo Lopes-Rocha; Eduardo Dias de Andrade (Universidade Estadual de Campinas, 2017)
Aim: the objective of this study was to evaluate the effect of betamethasone in the control of postoperative pain in patients undergoing endodontic treatment. Methods: patients of both genders (n = 120), after being submitted to emergency endodontic treatment, received a single dose of betamethasone solution (0.05 mg / body weight) or sterile saline solution intramucosally, in the periapical region of the treated tooth. The study evaluated the intensity of pain experienced by the patient and the number of analgesics consumed during periods of 4, 24 and 48 hours after endodontic treatment. To compare the level of pain among the groups and the use of analgesics the Fisher's Exact Test was used, adopting a significance level of 95%. Results: patients who received betamethasone felt less pain in 4 hours (p = 0.0177) and 24 hours (p = 0.0012) compared to those who received the placebo. Conclusions: betamethasone at a dose of 0.05 mg / body weight administered in the periapical region is a advantageous protocol due to its effectiveness, and also because of the comfort it provides to patients in the prevention or control of inflammatory pain in endodontics.